Investigation on the site preferences & magnetic properties of Co-doped SrAl4Fe8O19 hexaferrite - Shekhawat D.; Ahmad I.; Roy P.K. (My University, 2025)
The present work describes the structural and magnetic properties of partially Co substituted SrAl4CoxFe8-xO19 (0.0≤ x ≤ 0.6) ferrites. Single-phase strontium hexaferrite (p63/mmc) was synthesized by the sol-gel auto combustion method. The structural studies were carried out by the Rietveld analysis to get the information about the substituted sites of transition metal ions, bond length, and bond angle. Types of the bond were also explored through FTIR. EDX elemental analysis and mapping had also verified the presence of single-phase strontium hexaferrite. The effect of Co ion substitution on the magnetic properties was investigated with the help of a magnetic property measurement system (MPMS). The relationship between the occupancy of transition metal ions over the five sub-lattice sites was analyzed. The magneto-crystalline anisotropy was analyzed from the “Law of Approach to Saturation magnetization (Ms)” method. The oxidation state of the Co ion was also examined by the XAS spectra. The substitution of Co+3 enhanced the magnetization and permeability of the ferrites. Results indicated the significant dependency of Co+3 ion on the magnetic properties of strontium hexaferrite. © 2020 Elsevier B.V.